Detecting cognitive dysfunction in a busy multiple sclerosis clinical setting: a computer generated approach. (7th November 2013) - Lapshin, H.; Audet, B.; Feinstein, A.
<x xml:space="preserve">Abstract</x> Background and purpose This study aims to explore the effectiveness of a brief, computerized battery of tests in detecting cognitive differences between clinically isolated syndromes (CIS), relapsing−remitting multiple sclerosis (RRMS), primary progressive multiple sclerosis (PPMS) and secondary progressive multiple sclerosis (SPMS) patients. Methods Four groups of patients between the ages of 18 and 63 were enrolled from two hospital‐based multiple sclerosis clinics: CIS (n = 42), RRMS (n = 44), PPMS (n = 15) and SPMS (n = 37). All subjects were administered a validated battery of five computerized cognitive tests: the STROOP Color‐Word Test, the Computerized Symbol Digit Modalities Test, the Paced Visual Serial Addition Test (PVSAT) 4 s and 2 s trials, and a speed of cognition index obtained by subtracting simple reaction time from choice reaction time. Results were recorded by the test administrator. Results Significant between‐group differences in cognition were evident on all tests (P < 0.01) with the exception of the PVSAT 2 s trial. CIS patients were the least impaired, SPMS the most. RRMS and PPMS patients generally had a similar cognitive profile, more impaired than the CIS patients but less so than the SPMS patients. These differences persisted after controlling for the effects of age and education. Conclusions The ability of this computerized cognitive battery to distinguish the progression of cognitive deficits across the entire multiple sclerosis disease spectrum from CIS through to SPMS enhances its construct validity. This finding, coupled with the battery's brevity (20 min) and ease of administration, highlights its potential utility in a busy clinic setting.